Motivasi Kerja Dan Kompensasi Terhadap Kinerja Pegawai (Studi Kasus Badan Penanggulangan Bencana Daerah (BPBD) Kota Padang Panjang) - Rahmadia Rahmadia; Zusmawati Zusmawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The purpose of this research is to test the impact of work motivation variables on employee performance (Case Study of the Regional Disaster Management Agency (BPBD) Padang Panjang City, to test the impact of compensation variables on employee performance (Case Study of the Regional Disaster Management Agency (BPBD) Padang Panjang City. Data were collected through distributing questionnaires to 59 respondents using saturated sampling techniques, where all members of the population were sampled, using instrument tests (validity tests and reliability tests), descriptive analysis, classical assumption tests (normality tests, multicollinearity tests and heteroscedasticity tests) multiple linear regression and t test, with the help of the SPSS application. The results of the research show that work motivation has a positive and significant effect on employee performance (Case Study of the Regional Disaster Management Agency (BPBD) Padang Panjang City, compensation has a positive and significant effect on employee performance in (Study Case of the Padang Panjang City Regional Disaster Management Agency (BPBD). Which means the first hypothesis is accepted and the second hypothesis is accepted.